A Current Review on Polymeric Hydrogel Based: Pharmaceutical Sciences-Pharmaceutical analysis for Novel drug formulation - Kiruba, J. Subin; Arjun, Uppuluri Varuna Naga Venkata; T.S., Shanmugarajan (International Journal of Life Science and Pharma Research, 2021)
Skin tissue defects have become one of the major sources of mortality and morbidity among all age group people worldwide. Skin tissue engineering has enticed considerable heedfulness from researchers as an optimistic approach for repairing partial/ full thickness burn tissue. Skin is a highly vascularized, bio mineralized composite material composed of fibroblasts and collagen surrounded by specialized extracellular matrix with high mechanical strength and structural complexity. Although the auto grafts and allografts were regarded as the high attainment for wound repair, the approach was limited due to their inability revascularize and mimicking the damaged tissue. Further, the Polymeric hydrogels are very attractive skin tissue engineering scaffolds. The structural similarity of the polymeric hydrogels to the skin extracellular matrix provides additional benefits for non-invasive tissue repair. Owing to their poor healing ability, tissue regeneration was found to be challenging in skin tissue defects. However due to its excellent moisture retaining capabilities, biocompatibility and biodegradability several researchers shown considerable interest in potential applications of the hydrogels for skin tissue repair.Furthermore, recent progress involves the development of hydrogels with ideal mechanical and fast stimulus responsive characteristics. Moreover, hydrogels with structural similarity to the skin extracellular matrix up regulate the cell material interactions for quicker skin tissue repair and more regulated stimulus response changes in the microenvironment. This current review focused on the applications of both the synthetic and natural polymers involved in the formulation of the hydrogels for the skin tissue regeneration. Furthermore, understanding the polymers simultaneously reducing the complexity of building hydrogels should be the aim of the future research in the skin tissue regenerative medicine field.